On the role of oral feedback in ESL postgraduate thesis writing supervision - Abdulkhaleq, Mohammed Mohammed Ali; Abdullah, Faiz Sathi (Contemporary Research Center Australia, 2013)
The provision of oral feedback to ESL students at the postgraduate level plays an interventionist role in their development as writers. It is through such feedback that the students are expected to be guided towards achieving their writing goals. Supervisors provide written feedback and this is usually supported with oral feedback which appears to play a crucial role in the supervision process in that it helps in the formation of scholarly identities, scaffolds students' academic writing and learning, fosters autonomy, equality, and learning skills among ESL learners, develops students' dialogical skills, helps students focus on their research, and guides them to conform with dissertation/thesis writing. However, ESL students' own cultural background and social circumstances may affect the efficacy of the oral feedback process. Some limitations of existing studies are discussed and key directions for future research on the role of oral feedback in ESL postgraduate supervision settings are suggested.